Identifikasi Jenis Tumbuhan Liar sebagai Bahan Pangan di Sekitar Kawasan Suaka Margasatwa Kateri - Christine Naomi Panda Huki; Wihelmina Seran; Pamona Silvia Sinaga (Wana Lestari, 2024)
This study aims to determine the types of food source plants available and utilized by the community in the Kateri Wildlife Reserve area, Malacca Regency, East Nusa Tenggara Province in July 2023. The benefits of this research can provide information about wild plants as food and the utilization of wild plants as food. This research used snowball sampling technique or carried out sequentially by asking for information to people who had been interviewed previously through interviews, observations, and literature studies. Based on the results of the study, there were 15 plant species belonging to 11 families. Most of these families are the Fabaceae family. Each family has 6 species. The part used is the fruit part, which is 43 types. Where the percentage of leaves is the part of the plant used as much as 87% and the least used part, namely the stem 13%.